Particle board from wood waste with size particle (1.0 mm) in relation to different board density and resin content / Mohd Shuaib Azali Zulkepli - Zulkepli, Mohd Shuaib Azali (Faculty of Applied Sciences, 2016)
Logging activity can cause low soil and habitat protection expires wood annually increased demand has decreased. In addition, this material is quite popular nowadays have adopted one of the external and internal wood furniture alternatives particleboard. In these studies, the main purpose, to determine the mechanical and physical properties, from wood waste has been used for different densities of particle board and the circuit board and the resin content of the raw material used in manufacturing. Two different circuit board density are using; 650 kg 1m3 Iow-density board and 750 kg/m3 high density board. 8%, 10% and 12% resin content was used as another parameter using urea formaldehyde as a binder. The results showed that 12% of particleboard with a resin content of less than 750 kg/m3 density board bending strength and internal bonding and thickness swelling and water absorption, the lowest value to a higher value.